Developmental psychology : the school aged child - Strommen, E.A Ellen A. Strommen; McKinnry, J. P John Paul McKinney; Fitzgerald, H .E Hiram E. Fitzgerald (Illinois The Dorsey Press, 1983)
The book is about to study of how and why humans grow, change, and adapt across the course of their lives. Originally concerned with infants and children, the field has expanded to include adolescence, adult development, aging, and the entire lifespan. It also aim to explain how thinking, feeling, and behaviors change throughout life.
Includes bibliographical reference , glossary and index